Gut microbiome dysbiosis and increased intestinal permeability in children with islet autoimmunity and type 1 diabetes: A prospective cohort study. Issue 5 (20th May 2019) - Harbison, Jessica E.; Roth‐Schulze, Alexandra J.; Giles, Lynne C.; Tran, Cuong D.; Ngui, Katrina M.; Penno, Megan A.; Thomson, Rebecca L.; Wentworth, John M.; Colman, Peter G.; Craig, Maria E.; Morahan, Grant; Papenfuss, Anthony T.; et al.
Abstract: Aims/hypothesis: To investigate the longitudinal relationship between the gut microbiome, circulating short chain fatty acids (SCFAs) and intestinal permeability in children with islet autoimmunity or type 1 diabetes and controls. Methods: We analyzed the gut bacterial microbiome, plasma SCFAs, small intestinal permeability and dietary intake in 47 children with islet autoimmunity or recent‐onset type 1 diabetes and in 41 unrelated or sibling controls over a median (range) of 13 (2‐34) months follow‐up. Results: Children with multiple islet autoantibodies (≥2 IA) or type 1 diabetes had gut microbiome dysbiosis. Anti‐inflammatory Prevotella and Butyricimonas genera were less abundant and these changes were not explained by differences in diet. Small intestinal permeability measured by blood lactulose:rhamnose ratio was higher in type 1 diabetes. Children with ≥2 IA who progressed to type 1 diabetes (progressors), compared to those who did not progress, had higher intestinal permeability (mean [SE] difference +5.14 [2.0], 95% confidence interval [CI] 1.21, 9.07, P = .006), lower within‐sample (alpha) microbial diversity (31.3 [11.2], 95% CI 9.3, 53.3, P = .005), and lower abundance of SCFA‐producing bacteria. Alpha diversity (observed richness) correlated with plasma acetate levels in all groups combined (regression coefficient [SE] 0.57 [0.21], 95% CI 0.15, 0.99 P = .008). Conclusions/Interpretation: Children with ≥2 IA who progress to diabetes, like those with recent‐onset diabetes, have gut microbiome dysbiosis associated with increased intestinal permeability. Interventions that expand gut microbial diversity, in particular SCFA‐producing bacteria, may have a role to decrease progression to diabetes in children at‐risk.